Certidões de óbitos lavradas de sangue: a presença das miopias da branquitude no fluxo processual dos casos de mortes decorrentes da intervenção policial na cidade do Recife/PE. - Melo, Maria Adélia Gomes Correia de (2023)
The present work analyzes the procedural flow in cases of homicide of young people from cases filed in the justice system in 2018, launching the following research problem: to what extent is whiteness, present in the Criminal Justice System (SJC), directly linked to the constant cases of archiving of police investigations of cases resulting from deaths resulting from police intervention in Brazil? The theoretical framework that guides the interpretation of data is from critical criminology associated with the epistemological perspective of decoloniality. The objectives were to discuss the data produced on deaths in the country, the justifications for the lethal use of state force, as well as to identify procedural bottlenecks within the criminal justice system. To achieve the objective, methodologically, a bibliographical review was used, as well as the procedural flow methodology for quantitative mapping of processes within the scope of the criminal justice system and the Content Analysis (CA) methodology for the interpretation of qualitative data in relation to to the Criminal Justice System.